Verbal and Nonverbal Communication and Nigerian University Workplace Peacefulness - Uwatt, Louisa Etebom; Timothy, Alexander Essien; Obiekezie, Eucharia; Uguma, Vincent Ugah; Ironbar, Virginia Emmanuel; Ukume, Gladys (International Journal of Membrane Science and Technology, 2023)
The study investigated Nigerian university workers’ perceptions of the verbal and non-verbal communication variables that are important to workplace peace. The study used a mixed methodology with poetic inquiry triangulated with quantitative methodology. The researchers posed and answered seven research questions. The data were collected through a semi-structured questionnaire constructed using Google Forms, from where the qualitative data were extracted and analysed using thematic and structural coding. The quantitative data analysis was done using simple percentages. The results showed that communication could engender conflict when it is improper, disrespectful, insensitive, inconsiderate and poorly channelled. For verbal communication, participants considered fluency and appropriate choice of words as very important to workplace peace. For non-verbal communication, politeness, attentiveness, and greetings were rated as most important to workplace peace. Civility and communication training were recommended for university staff.